A Pragmatic Analysis of the Speech Act of Supplication in the Holy Quran: Pragmatics - Khazaleh, Hekmat Abed Daifallah; Sapar, Ahmad Arifin; Mohd Jan, Jariah (Al-Ḍād Journal, 2023)
The current study aims at exploring the speech act of supplication in the Glorious Quran namely, the supplicants, the syntactic forms used in the Quran for supplication and its illocutionary force based on Searle's Speech Act Theory. To attain the main purpose of the current study, different syntactic forms of Quranic supplication are investigated based on the categories of the supplicants. The analysis is built upon the relationship between the addresser and the addressee, the situational context, and the lexical choices employed for supplication. Besides, the felicity conditions and the direction of fit are highlighted for explanatory purposes. Findings showed that the Quranic supplications are employed by angels, prophets, believers, unbelievers, Satan, Adam and Eve. Further, supplication is classified as a directive speech act based on Searle's taxonomy. However, the syntactic structures of imperatives, negative-imperatives, interrogatives, conditionals, and declaratives are used for the locutionary act of supplication. Thus, supplication can be classified as both direct directive and indirect directive. Keywords: Glorious Quran; supplication; Speech Act Theory; Indirect directive; direct directive